2022
DOI: 10.1039/d2ob00082b
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the tandem copper-catalyzed Ullmann–GoldbergN-arylation–cyclization strategies

Abstract: N‒Aryl bond formation under copper catalysis has been playing a pivotal role and has been extensively used as a key step in the total syntheses of several therapeutic molecules. The...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 194 publications
0
5
0
Order By: Relevance
“…7 With convenient access to the heterocycles in hand, we planned to convert benzoxazolpyrroles, benzothiazolpyrroles and indolizines derived from 2-bromobenzaldehydes into indole-fused heterocyclic compounds via intramolecular N -arylation reactions. 8 A short screening of the conditions for the intramolecular N -arylation of 4s revealed that the best results were obtained under Buckwald–Hartwig amination 9 conditions: 10 mol% Pd(OAc) 2 , 20 mol% SPhos, 2.5 equiv. LiO t Bu in toluene at 150 °C, and 18 h (entry f, Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…7 With convenient access to the heterocycles in hand, we planned to convert benzoxazolpyrroles, benzothiazolpyrroles and indolizines derived from 2-bromobenzaldehydes into indole-fused heterocyclic compounds via intramolecular N -arylation reactions. 8 A short screening of the conditions for the intramolecular N -arylation of 4s revealed that the best results were obtained under Buckwald–Hartwig amination 9 conditions: 10 mol% Pd(OAc) 2 , 20 mol% SPhos, 2.5 equiv. LiO t Bu in toluene at 150 °C, and 18 h (entry f, Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the interesting structure of 1,1′-bisindoles and the limited number of synthetic routes to this class of compounds, we decided to develop a new synthetic approach to symmetric 1,1′-bisindoles which is based on the reaction between one 1,2-bis(2-bromoaryl)hydrazine and two acyclic 1,3-diketones in terms of a Cu-catalyzed double domino condensation/intramolecular Ullmann type C–C coupling (Scheme 1). 34–37…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, Cu-catalyzed C–N coupling reactions using boronic species (Chan–Lam–Evans coupling) have gained great attention and also provided an array of coupling/annulation cascade reactions. 14 Thus, it was questioned whether anthranils could be converted to acridines directly via a sequential amination/annulation process in one-pot vessels using arylboronic acids, 15 which would provide a more step-economical approach for the synthesis of acridines. To achieve this, a clear obstacle was the merging of distinctly different reaction conditions of these two steps, one basic and the other acidic.…”
Section: Introductionmentioning
confidence: 99%